2005
DOI: 10.1071/ar04140
|View full text |Cite
|
Sign up to set email alerts
|

The development of an improved PCR-based marker system for Sw-5, an important TSWV resistance gene of tomato

Abstract: Abstract. Sw-5 is an important disease resistance gene of tomato, providing broad resistance to Tomato spotted wilt virus (TSWV). A cleaved amplified polymorphic sequence (CAPS) marker, closely linked to the gene, has been reported. Although the Sw-5 locus has been characterised, a gene-specific marker has not been developed. This paper presents a PCR-based marker-system that consists of the co-amplification of a dominant marker representing the Sw-5 gene sequence, and the modified CAPS marker as a positive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
1
12
0
2
Order By: Relevance
“…The tospovirus resistance protein A of the gene Sw5-a is complement to the sequence of the Sw-5 locus located at AY007366 from 20824 to 24561 base and the tospovirus resistance protein B of the gene Sw5-b is complement to the sequence of the Sw-5 locus located at AY007366 from 29513 to 33253 base (Folkertsma et al1999, GenBank Accession AY007366). Garland et al (2005) reported a dominant PCR-based marker representing the Sw-5 gene sequence co-segregated with the RFLP marker CT 220 (Stevens et al 1995(Stevens et al , 1996 in 50 individuals of an F 2 mapping population.…”
Section: Introductionmentioning
confidence: 99%
“…The tospovirus resistance protein A of the gene Sw5-a is complement to the sequence of the Sw-5 locus located at AY007366 from 20824 to 24561 base and the tospovirus resistance protein B of the gene Sw5-b is complement to the sequence of the Sw-5 locus located at AY007366 from 29513 to 33253 base (Folkertsma et al1999, GenBank Accession AY007366). Garland et al (2005) reported a dominant PCR-based marker representing the Sw-5 gene sequence co-segregated with the RFLP marker CT 220 (Stevens et al 1995(Stevens et al , 1996 in 50 individuals of an F 2 mapping population.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the 'Sw-5-2' co-dominant, within-locus, SCAR marker system is more advantageous than the other closely linked markers reported thus far. In addition, the SCAR marker reported here is much simpler than the CAPS marker system reported by Garland et al (2005), which requires the use of the closely linked CT220 marker as a positive control in order to discriminate susceptible plants from false negative PCR reactions (Garland et al 2005). It is important to mention that the amount of sequence variation observed in the genomic region encompassing this polymorphic amplicon might allow the further development of even better markers potentially suitable for gel-free systems.…”
Section: Resultsmentioning
confidence: 99%
“…These are closely linked markers, which might occasionally be separated from the gene of interest through genetic recombination (crossing-over) events. In this scenario, markers derived from the resistant locus itself, capable of differentiating among susceptible and resistant plants, would be the ideal ones (Folkertsma et al 1999;Garland et al 2005). Although sequences of the Sw-5 locus are available at public databases, there are few reports of molecular markers derived from them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for TSWV resistance conferred by the Sw-5b gene, diverse molecular markers such as RAPD (random amplified polymorphic DNA), RFLP, SCAR (sequence characterized amplified regions), CAPS, and INDEL markers have been reported (Dianese et al, 2010;Garland et al, 2005;Langella et al, 2004;RosellĂł et al, 2001;ƚmiech et al, 2000;Stevens et al, 1995). Since the successful cloning of the Sw-5b gene, a gene-based marker and two SNPs specific to the Sw-5b allele for TSWV resistance have been reported (Shi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%